Expression of the primate-specific LINC00473 RNA in mouse neurons promotes excitability and CREB-regulated transcription - Pruunsild, Priit; Bengtson, C. Peter; Loss, Isabel; Lohrer, Benjamin; Bading, Hilmar (The journal of biological chemistry, 2023)
The LINC00473 (Lnc473) gene has previously been shown to be associated with cancer and psychiatric disorders. Its expression is elevated in several types of tumors and decreased in the brains of patients diagnosed with schizophrenia or major depression. In neurons, Lnc473 transcription is strongly responsive to synaptic activity, suggesting a role in adaptive, plasticity-related mechanisms. However, the function of Lnc473 is largely unknown. Here, using a recombinant adeno-associated viral vector, we introduced a primate-specific human Lnc473 RNA into mouse primary neurons. We show that this resulted in a transcriptomic shift comprising downregulation of epilepsy-associated genes and a rise in cAMP response element-binding protein (CREB) activity, which was driven by augmented CREB-regulated transcription coactivator 1 nuclear localization. Moreover, we demonstrate that ectopic Lnc473 expression increased neuronal excitability as well as network excitability. These findings suggest that primates may possess a lineage-specific activity-dependent modulator of CREB-regulated neuronal excitability.
Online verfügbar: 3. April 2023, Artikelversion: 2. Mai 2023
Gesehen am 08.08.2023